Drought and vegetation analysis in Tarsus River Basin (Southern Turkey) using GIS and Remote Sensing data - Duran, Celalettin (Uluslararasi Insan Bilimleri Dergisi, 2015)
In this study, the effects of topographic variables on drought and vegetation in dry season have been examined. Distributions of dry conditions in Tarsus River Basin were derived using the NDVI, NDMI indexes and LST (Land Surface Temperature) from landsat8 image bands. There is large difference in elevation in the study area. Local climatic conditions are formed under the influence of altitude and morphological structure. Narrow and deep valleys in the topography create more moderate temperature/moisture conditions and are the main distribution area of tall forest vegetation. High radiation in the highest plateau system and, extreme temperature/moisture values led short-lived herbaceous vegetation to spread. Due to high insolation/temperature and restricted marine affect, establishment of scrub vegetation can be observed both in mid-elevation and south-sloping plateau of the study area. Anthropogenic agricultural fields form the land surface with the potential of high temperature/evapotranspiration rate in harvesting periods. Broadleaf plant species spread in areas close to the base of the valley stream. Plantation forest has been created in areas of near-shore sand dunes and very small delta (marsh). Variability in topography also increases the width of the combination of factors that shape the vegetation. This also enables the number of taxa to increase and unusual taxa to co-exist.
Keywords: Moisture; Tarsus River Basin; Temperature; Topography; Vegetation; Physical Geography; Climatic Geomorphology; Vegetation; Geography; Geomorphology; Remote Sensing; 13. Climate action; 15. Life on land; 6. Clean water